The Effect of Continuous and Interval Aerobic Exercise Combined with Loquat Leaf Consumption on the Oxidative and Antioxidant Capacity in Overweight Women - Afshari Fard, Nahid; Banai, Jamshid; Eftekhari , Elham; Keshavarz, Saeed (Health Nexus, 2025)
The present study aimed to determine the effect of continuous and interval aerobic exercise combined with loquat leaf consumption on the oxidative and antioxidant capacity in overweight women. The research method was quasi-experimental, with a pre-test and post-test design. Sixty overweight women from Qom city were purposefully divided into four equal groups of 15 participants: continuous aerobic exercise, interval aerobic exercise, continuous aerobic exercise combined with loquat leaf consumption, and interval aerobic exercise combined with loquat leaf consumption. The exercise protocol was conducted over eight weeks with three sessions per week. The continuous aerobic exercise program included continuous running without rest at an intensity of 55-60% of the heart rate reserve. The interval training program consisted of interval runs at distances of 100, 200, 300, 400, and 600 meters, with an intensity of 80-85% of the heart rate reserve. Data were analyzed using ANCOVA and Tukey’s post-hoc test. The findings showed that continuous aerobic exercise combined with loquat leaf consumption significantly affected the oxidative capacity of overweight women. ANCOVA results indicated a significant difference in oxidative capacity between the four groups. Bonferroni post-hoc test results revealed a significant difference between the continuous and interval exercise groups and the two combined groups (continuous exercise with supplementation and interval exercise with supplementation). Additionally, the results demonstrated that aerobic exercise combined with loquat leaf consumption significantly affected the antioxidant capacity of overweight women. ANCOVA results indicated a significant difference in antioxidant capacity between the four groups, rejecting the null hypothesis and confirming the research hypothesis. The Bonferroni post-hoc test results further revealed a significant difference between the continuous and interval exercise groups and the two combined groups (continuous exercise with supplementation and interval exercise with supplementation). Based on the results, the combination of continuous and interval aerobic exercise with loquat leaf consumption is an effective method for improving the oxidative and antioxidant capacity in overweight women.